Fabrication and characterization of dexibuprofen nanocrystals using microchannel fluidic rector - Khan J; Bashir S; Khan MA; Mohammad MA; Isreb M (Dove Medical Press, 2018)
Jahangir Khan,1–3 Sajid Bashir,1 Muhammad Asif Khan,4 Mohammad Amin Mohammad,3 Mohammad Isreb3 1Department of Pharmacy, Faculty of Pharmacy, University of Sargodha, Sargodha, Pakistan; 2Department of Pharmacy, University of Malakand, Dīr, Khyber Pakhtunkhwa, Pakistan; 3School of Pharmacy, Institute of Life Science Research, School of Pharmacy, University of Bradford, Bradford, UK; 4Department of Pharmacy, Sarhad University Peshawar, Peshawar, Pakistan Purpose: Dexibuprofen is an enantiomer of ibuprofen with low bioavailability which results from its hydrophobic nature. Nanosuspensions have developed a podium to solve the in vitro dissolution problem that frequently occurs in current research. Materials and methods: The drug and polymer solutions were mixed in a microchannel fluid reactor and the successive embryonic nanosuspension was decanted into a vial having the polymer solution. The impact of different process and formulation parameters including inlet angle, antisolvent and solvent flow rate(s), mixing time, drug concentration, polymer type and concentration was evaluated. Results and discussion: Stable dexibuprofen nanocrystals with a particle size of 45±3.0 nm and polydispersity index of 0.19±0.06 were obtained. Differential scanning calorimetry and powder X-ray diffraction confirmed the crystallinity. The key parameters observed were inlet angle 10°, antisolvent to solvent volume of 2.0/0.5 mL/min, 60 minutes mixing with 5 minutes sonication, Poloxamer-407 with a concentration of 0.5% w/v and drug concentration (5 mg/mm). The 60-day stability studies revealed that the nanocrystals were stable at 4°C and 25°C. The scanning electron microscopy and transmission electron microscopy images showed crystalline morphology with a homogeneous distribution. Conclusion: Stable dexibuprofen nanocrystals with retentive distinctive characteristics and having marked dissolution rate compared to raw and marketed formulations were efficiently fabricated. In future perspectives, these nanocrystals could be converted to solid dosage form and the process can be industrialized by chemical engineering approach. Keywords: nanocrystal, dexibuprofen, microchannel fluidic reactor, process and formulation parameters